Considerations Regarding the Legal Nature of the Maintenance Contract in the Law of Certain European States - Iliescu, Alina-Elena (Acta Universitatis Danubius. Juridica, 2025)
Considering past issues regarding the qualification of maintenance contracts concluded free of charge - explicitly provided for in the current Romanian Civil Code - and regarding the application of norms from the field of life annuity contracts, as well as the “specific rules of the legal act of constitution” free of charge, we aimed to find another response to these matters in the legal systems of other European states, obviously belonging to the major continental legal system. Therefore, we focused on the classification of various “maintenance contracts” (the terms are not identical, sometimes not even similar, and terminological differences are inherent) into the category of onerous contracts—implicitly within the subcategory of aleatory ones—or gratuitous ones. We primarily considered French law, given its influence on the other analysed legal systems, including Romanian law, and also the fact that French doctrine and jurisprudence have given greater attention to aleatory contracts, implicitly to the one analysed. Furthermore, we also studied the legal norms, specialized literature opinions, and judicial practices of states with a tradition regarding the conventional obligation of maintenance.